Improving Digital Literacy of Sukadarma Village Community in Promoting Products Online - Agustianingsih, Amelia; Rahayu, Andini Julia; Zahro, Fatimahtuz; Cahyadi, Adit; Chandra Saputra, Riky; Santoso, Miftah Faroq (Society : Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has created significant opportunities for micro, small, and medium enterprises (MSMEs) to expand their markets through online marketing. However, many MSMEs in Sukadarma Village, Sukatani District, still face challenges in adopting digital marketing strategies due to low digital literacy and limited access to information. This community service activity aims to enhance the understanding and skills of local MSME actors in digital marketing through intensive training and mentoring. The methods used include socialization, hands-on training, and achievement evaluation through pre-tests and post-tests. The results show an improvement in participants' understanding of utilizing social media and marketplaces for product marketing. Additionally, there was an increase in customer interaction with products marketed digitally. Challenges encountered include differences in participants' digital literacy levels and limited internet access in some areas, which were addressed through additional mentoring. The sustainability of this program is expected to be strengthened through the formation of a local digital marketing community and collaboration with e-commerce platforms and internet service providers. Thus, strengthening digital literacy among MSMEs in this village can contribute to enhancing competitiveness and economic growth within the community.